Program Edukasi Budaya Nusantara melalui Pembelajaran Tarian Daerah di SB Pandan Jaya Malaysia - Nurmaulidia Husaeni; Edy Purwanto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Indonesian immigrant children growing up in Malaysia often have limited structured exposure to Nusantara culture within informal learning environments. Traditional regional dance offers strong pedagogical value, yet its impact must extend beyond movement imitation to foster cultural literacy. This study aimed to evaluate the effectiveness of a blended cultural learning activity in strengthening Nusantara cultural literacy through regional dance education at Sanggar Bimbingan Pandan Jaya, Malaysia. A blended activity method was used, including (1) cultural stimulus through traditional dance videos, (2) cognitive reinforcement using gamified quizzes on dance names and regional origins, and (3) stepwise guided dance practice emphasizing rhythm, expression, and movement synchronization. Data were collected through observation, quiz scores, and movement evaluation rubrics involving 20 students (grades 3–6). Results show that videos increased engagement and cultural recognition, quizzes improved immediate factual recall accuracy, and 80% of participants could follow fundamental dance movements with adequate rhythmic synchronization after guided demonstrations. Participants also displayed rising confidence, cultural pride, and a developing sense of belonging toward Indonesian cultural roots.